ANATOMICAL PROPERTIES OF Shorea mujongensis P.S. Ashton, A CRITICALLY ENDANGERED SPECIES OF DIPTEROCARPS FROM KALIMANTAN - Listya Mustika Dewi; Supartini Supartini (Indonesian Journal of Forestry Research, 2011)
Wood anatomy of Shorea mujongensis P.S. Ashton was investigated in order to ensure this species belongs to yellow meranti group. Such study is very important since this species is already listed in the red list of IUCN and classified as critically endangered species. The microscopic slides were prepared according to the Johansen's method, while the anatomical features observed according to the IAWA  List. The results show that S. mujongensis wood exhibit brown heartwood, light brown sapwood, rough texture, straight grain sometimes interlocked and somewhat rough. The main microscopic characters are growth rings indistinct; vessel diffuse, mostly solitary, rounded to oval; simple perforation plate and alternate intervessel pits; parenchyma scanty paratracheal to thin vasicentric; axial intercellular canals in long tangential line, radial intercellular canal and vasicentric tracheids present; rays uniseriate and multiseriate, prismatic crystal in procumbent cells; fiber length 1,294 µm, diameter 26 µm and wall thickness 4µm. Macroscopic and microscopic observation of S. mujongensis wood confirms the species belongs to yellow meranti group. The assesment on fiber dimensions and derived values of the wood fibers classified the wood into class quality II. It indicates that this species is moderately favorable as raw material for pulp and paper manufacture.